ABOUT IMPROVEMENT OF TECHNOLOGICAL PROPERTIES OF COSMETIC DRY BUILDING MIXTURES - Turgunbaev Urinbek; Murtozoev Eshmurod (Scholar Express Journal, 2021)
Our research on this topic is aimed at developing the technology of DCM based on local raw materials, in particular dewatered clay, quicklime, sand, soda ash and additives. This article presents some of the results of our research on the selection of the composition of such DCM
Keywords: raw materials; dewatered clay; quicklime; sand